2023
DOI: 10.2147/ijn.s426703
|View full text |Cite
|
Sign up to set email alerts
|

The Self-Assembly Soluplus Nanomicelles of Nobiletin in Aqueous Medium Based on Solid Dispersion and Their Increased Hepatoprotective Effect on APAP-Induced Acute Liver Injury

Jinrong Ning,
Guodong Zheng,
Yi Cai
et al.

Abstract: Purpose APAP-induced liver injury (AILI) is a common cause of acute liver failure (ALF). Nobiletin (NOB) is a potential hepatoprotective agent for the treatment of APAP-induced liver injury. However, the poor solubility and low bioavailability of NOB hinders its application. In this study, a novel self-assembly nano-drug delivery system of nobiletin (solid dispersion of NOB, termed as NOB/SD) was developed based on solid dispersion technology to improve the bioavailability and hepatoprotective abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…AILI accounts for 39% and 57% of acute liver failure cases in the USA and UK, respectively. Several studies have reported NOB’s protective effects and possible mechanisms in AILI ( Figure 2 ) ( Lin et al, 2019 ; Guvenc et al, 2020 ; Ning et al, 2023 ). In the AILI model in rats pretreated with NOB (10 mg/kg) for 10 days, NOB significantly enhanced anti-oxidative stress and anti-inflammatory protective effects by inducing HO-1 and Nrf-2 expression, attenuating liver injury ( Guvenc et al, 2020 ).…”
Section: Nob Ameliorates Acute Liver Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…AILI accounts for 39% and 57% of acute liver failure cases in the USA and UK, respectively. Several studies have reported NOB’s protective effects and possible mechanisms in AILI ( Figure 2 ) ( Lin et al, 2019 ; Guvenc et al, 2020 ; Ning et al, 2023 ). In the AILI model in rats pretreated with NOB (10 mg/kg) for 10 days, NOB significantly enhanced anti-oxidative stress and anti-inflammatory protective effects by inducing HO-1 and Nrf-2 expression, attenuating liver injury ( Guvenc et al, 2020 ).…”
Section: Nob Ameliorates Acute Liver Injurymentioning
confidence: 99%
“…NOB/SD displayed significantly enhanced bioavailability in healthy Sprague Dawley rats in vivo . Furthermore, NOB/SD alleviated AILI by improving anti-oxidative stress with ROS scavenging and Nrf2 activation ( Ning et al, 2023 ).…”
Section: Nob Ameliorates Acute Liver Injurymentioning
confidence: 99%